2018
DOI: 10.1096/fasebj.2018.32.1_supplement.lb112
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood mitochondrial DNA copy number, a potential marker of non‐alcoholic fatty liver disease?

Abstract: IntroductionNonalcoholic fatty liver disease (NAFLD) includes a spectrum of histological findings ranging from simple steatosis (SS) to non‐alcoholic steatohepatitis (NASH). Although often considered the hepatic manifestation of metabolic syndrome (MS), longitudinal studies suggest that NAFLD precedes MS. To date, liver biopsy is the most accurate method to differentiate between SS and NASH. However, recent studies indicate an association between mitochondrial DNA (mtDNA) copy number and NAFLD severity in live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This can have several reasons, for example, beside limited number of samples, our studies had a case-control design and we did not investigate liver mtDNA-CN in individuals through long duration of time. Also, evidence indicated that mtDNA-CN can vary between different cell types and answer differently to various physiologic and pathologic states including NAFLD ( Tapia et al, 2018 ; Ma et al, 2020 ; Filograna et al, 2021 ) suggesting a dynamic nature for this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…This can have several reasons, for example, beside limited number of samples, our studies had a case-control design and we did not investigate liver mtDNA-CN in individuals through long duration of time. Also, evidence indicated that mtDNA-CN can vary between different cell types and answer differently to various physiologic and pathologic states including NAFLD ( Tapia et al, 2018 ; Ma et al, 2020 ; Filograna et al, 2021 ) suggesting a dynamic nature for this parameter.…”
Section: Discussionmentioning
confidence: 99%